2018
DOI: 10.1175/jcli-d-17-0665.1
|View full text |Cite
|
Sign up to set email alerts
|

Model Uncertainty in Cloud–Circulation Coupling, and Cloud-Radiative Response to Increasing CO2, Linked to Biases in Climatological Circulation

Abstract: Recent analyses of global climate models suggest that uncertainty in the coupling between midlatitude clouds and the atmospheric circulation contributes to uncertainty in climate sensitivity. However, the reasons behind model differences in the cloud–circulation coupling have remained unclear. Here, we use a global climate model in an idealized aquaplanet setup to show that the Southern Hemisphere climatological circulation, which in many models is biased equatorward, contributes to the model differences in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
3
5
0
Order By: Relevance
“…This result is similar to that of Lipat et al (2017, 2018), who found that an equatorward‐biased Hadley cell edge in models leads to incorrect radiative responses to poleward shifts of the circulation features as a result of climate change. Furthermore, the results in Figure 4 provide a cautionary example of the limitations of combining sensitivities of cloud properties to dynamical cloud‐controlling factors from observations with changes in those cloud‐controlling factors from GCMs using a multiple linear regression model.…”
Section: Summary and Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This result is similar to that of Lipat et al (2017, 2018), who found that an equatorward‐biased Hadley cell edge in models leads to incorrect radiative responses to poleward shifts of the circulation features as a result of climate change. Furthermore, the results in Figure 4 provide a cautionary example of the limitations of combining sensitivities of cloud properties to dynamical cloud‐controlling factors from observations with changes in those cloud‐controlling factors from GCMs using a multiple linear regression model.…”
Section: Summary and Discussionsupporting
confidence: 90%
“…The solid lines in Figure 4(a) and (b) show the CMIP6 multi‐model‐mean zonal‐mean SWCRE anomalies associated with a poleward shift in the SH midlatitude jet and Hadley cell extent. The models reproduce the positive SWCRE anomaly at SH midlatitudes associated with a poleward shift in the SH Hadley cell extent (Figure 4(b), compare solid and dashed lines), although they overestimate its magnitude compared to observations (see also Lipat et al 2017, 2018). In contrast, the models also produce a positive SWCRE anomaly at SH midlatitudes associated with a poleward shift in the SH midlatitude jet (Figure 4(a), compare solid and dashed lines), which does not occur in observations (Grise & Polvani 2014; GM16).…”
Section: Summary and Discussionmentioning
confidence: 72%
“…Lipat et al. (2018) also showed modeling evidence that poleward expansion of the Hadley circulation causes stronger middle‐tropospheric subsidence and enhanced lower‐tropospheric stability between about 35° and 55°S. We find that SAM variations are related to anomalies of tropopause pressure, middle‐tropospheric vertical motion, and lower‐tropospheric stability in ways that are consistent with these studies (Figure S1 in Supporting Information ).…”
Section: Response Of Cloud Radiative Heating To the Samsupporting
confidence: 90%
“…Third, 𝐴𝐴 𝐴𝐴 anomalies below 1.5 km coincide with anomalous low-level static stability, suggesting that they may result from anomalies of the inversion strength at the top of the planetary boundary layer. Lipat et al (2018) also showed modeling evidence that poleward expansion of the Hadley circulation causes stronger middle-tropospheric subsidence and enhanced lower-tropospheric stability between about 35° and 55°S. We find that SAM variations are related to anomalies of tropopause pressure, middle-tropospheric vertical motion, and lower-tropospheric stability in ways that are consistent with these studies (Figure S1 in Supporting Information S1).…”
Section: Response Of Cloud Radiative Heating To the Samsupporting
confidence: 89%
“…Another area of progress is new understanding the role of cloud radiative effects in shaping the mid-latitude circulation response to anthropogenic forcing. Through their non-uniform distribution of radiative heating, cloud changes can modify meridional temperature gradients and alter mid-latitude circulation and the annular modes in both hemispheres (Ceppi et al, 2014;Voigt andShaw, 2015, 2016;Ceppi and Hartmann, 2016;Ceppi and Shepherd, 2017;Lipat et al, 2018;Albern et al, 2019;Voigt et al, 2019). In addition to the effects of changing upper and lower tropospheric temperature gradients on the NAM, progress has been made since AR5 in understanding the effect of simulated changes in the strength of the stratospheric polar vortex on winter NAM projections (Manzini et al, 2014;Zappa and Shepherd, 2017;Simpson et al, 2018).…”
Section: Northern Annular Modementioning
confidence: 99%